Nice work – but wrong label - Shrestha, Krishna K. (Himalayan Journal of Sciences, 2006)
Review of "Himalayan Botany in the Twentieth and Twenty-first Centuries" By S. Noshiro, and K.R. Rajbhandari (eds.) The Society of Himalayan Botany Tokyo, Japan, 2002 212 pp. ISBN 4-9900825-2-4 Price not mentioned The book cannot claim to be a history of Himalalyan flora for two reasons: first, it basically deals with history of Nepal-Japan collaboration rather than with botanical advancement, and second, the taxonomic development is exclusively confined within the last 40 years' period. Himalayan Journal of Sciences 1(1): 15-16, 2003 The full text is of this article is available at the Himalayan Journal of Sciences website